THE ROLE AND IMPORTANCE OF CORPORATE BONDS IN FINANCING THE PRIVATE SECTOR - Khushvakov Islombek Mukhammadi ogli (Scholar Express Journals, 2025)
Corporate bonds serve as a vital financing tool for private sector development, particularly in emerging economies where traditional bank lending is often limited or expensive. This paper examines the significance of corporate bonds in mobilizing long-term capital, reducing dependency on banks, and promoting financial transparency and corporate governance. It reviews global and regional trends, highlighting how well-developed bond markets support investment in key sectors such as infrastructure, manufacturing, and innovation. The study also identifies regulatory challenges, investor behavior, and market infrastructure as critical factors shaping the growth of corporate bond markets. Findings suggest that appropriate policy frameworks and institutional reforms can enhance corporate bond issuance, attract foreign investment, and improve macroeconomic stability. Overall, the paper emphasizes the importance of fostering strong corporate bond markets to meet the rising financial needs of the private sector in today’s global economy.
Keywords: Corporate bonds; private sector